'Why, why did you have me treated?': the psychotic experience in a literary narrative. Issue 2 (4th August 2011) - Kaptein, A A; Koopman, J J E; Weinman, J A; Gosselink, M J
Abstract : In this paper, the authors suggest an approach that may be helpful in teaching medical humanities to medical students. In the context of an honours class on medicine and literature, students (1) read a novel on an illness, (2) interviewed a patient with the medical condition described in the novel and (3) wrote an essay on the biomedical, narrative and literary aspects of these sources of information. The authors compared the story of Chekhov's literary protagonist Kovrin in The Black Monk with the personal story of patient H., who was diagnosed with schizophrenia. The narratives of the two patients were compared, based on Chekhov's literary narrative and the narrative of the patient. Both patients appeared to somehow regret losing their symptoms, following various psychiatric treatments. Both narratives show the ambivalence between the gain and loss that adequate psychiatric treatment may bring. Studying novels and other literary sources may help in understanding the story of the patient better, with associated improvements in various aspects of medical outcome. Reading literary fiction may help to increase an understanding of patients' emotions, experiences, cognitions and perspectives. It may also reduce the emotional distance between the self and the patient. The educational approach that was explored in the authors' honours class may be helpful to others when developing methods for teaching medical humanities to (medical) students.